2023
DOI: 10.1002/mus.27815
|View full text |Cite
|
Sign up to set email alerts
|

Neuroregeneration and immune response after neurorrhaphy are improved with the use of heterologous fibrin biopolymer in addition to suture repair alone

Abstract: Introduction/Aims: Peripheral nerve injuries result in impaired neuromuscular interactions, leading to morphological and functional alterations. Adjuvant suture repair methods have been used to improve nerve regeneration and modulate the immune response. Heterologous fibrin biopolymer (HFB), a scaffold with adhesive properties, plays a critical role in tissue repair. The aim of this study is to evaluate neuroregeneration and immune response focusing on neuromuscular recovery, using sutureassociated HFB for sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…1,30 In experimental models, intramuscular connective tissue infiltration and decreased muscle weight and area may act as possible indicators of muscle degeneration. [31][32][33] In our muscle tissue analysis, the numbers of muscle fibers with central nuclei were higher in the S and R groups when compared with C. Usually, myonuclei occupy the periphery of the myofibrils, whereas in pathological conditions the presence of central nuclei is higher. 34 Central nuclei usually appear after damage induced by a variety of injuries, including exposure to myotoxic drugs.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…1,30 In experimental models, intramuscular connective tissue infiltration and decreased muscle weight and area may act as possible indicators of muscle degeneration. [31][32][33] In our muscle tissue analysis, the numbers of muscle fibers with central nuclei were higher in the S and R groups when compared with C. Usually, myonuclei occupy the periphery of the myofibrils, whereas in pathological conditions the presence of central nuclei is higher. 34 Central nuclei usually appear after damage induced by a variety of injuries, including exposure to myotoxic drugs.…”
Section: Discussionmentioning
confidence: 62%
“…Magnetic resonance imaging studies in the lower limbs of patients affected by myopathy, including of anti–HMG‐CoA antibodies, the presence of which suggests SAMS, revealed generalized muscle edema of the affected musculature, fat infiltration due to inflammation, and fiber necrosis 1,30 . In experimental models, intramuscular connective tissue infiltration and decreased muscle weight and area may act as possible indicators of muscle degeneration 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…The methodology used in this experimental protocol was based on previous studies by our group on peripheral nerve regeneration, causing an injury to the buccal branch of the facial nerve in rats [ 37 , 38 , 83 ]. In these studies, it was proven that HFB has the capacity to allow the repair of the lesion with results similar to the gold standard of end-to-end neurorrhaphy, which uses suture thread [ 84 , 85 ]. In an unprecedented way, in the present study, we evaluated a protocol with a smaller number of PBM sessions and also the effects on facial muscles, through morphofunctional analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we demonstrated the early beneficial effects of the use of HFB in conjunction with two sutures for the repair of transected sciatic nerves in rats [ 13 ]. HFB application in comparison to suture alone improved overall nerve regeneration, with increased axonal growth and tissue vascularization (angiogenesis), proper restoration of neuromuscular junctions, reduced severe muscle degeneration (collagen infiltration), and enhanced relative area of M2 markers, 7 and 30 days after reconstruction.…”
Section: Hfb In Nerve Repairmentioning
confidence: 99%
“…The use of HFB as an adjunct in peripheral and central nerve reconstruction has been showing promising results through the development of an immunomodulatory and neuroprotective environment at the injury site [ 10 - 13 ] and has also been applied in various other experimental models of reconstructive surgery [ 7 , 14 ]. The use of HFB has already been experimentally shown to provide a microenvironment of stability and protection at the reconstruction site, leading to positive scenarios of nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%